Development of electric stove for smart use of Solar Photovoltaic energy with national grid - Islam, Md. Shariful; Azad, Md. Sabbir Bin; Rongon, Humayra Fakir (BRAC University, 2014)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2013.